Smart Temperature Sensor Hot Water Cylinder Demand Management - Struwig, Christian Karl (Wellington Faculty of Engineering Symposium, 2023)
The growth of residential electricity consumption in Aotearoa urges for the improvement of existing demand management technologies. Expensive technologies like Ripple Control externally control residential electric hot water cylinders to help manage demand. This paper presents and evaluates an affordable alternative hot water controller by using an energy harvesting Internet of Things temperature control sensor found at the outlet pipe of a hot water cylinder. The control sensor is charged by harvesting the thermal energy from the temperature gradient between the outlet pipe and the ambient air using mounted Thermoelectric Generators, or TEGs. Using Bluetooth Low-Energy the control sensor relays accurate temperature readings of the stored hot water. The control sensor’s power electronic interface for the TEGs is a low power DC-DC boost converter that charges a lithium- ion battery. The controls sensor’s estimated energy consumption was simulated and used for the design and development of the device. The expected energy consumption was later evaluated with the recorded consumption. Thermal data gathered from an electric hot water cylinder and thermal modelling software were used to evaluate the performance of the TEGs to be selected meeting the energy demands of the control sensor. The boost converter design was simulated and developed. The real performance of the boost converter and TEGs were then tested and evaluated with the simulated results. The paper investigates the lifetime, temperature reading accuracy and network performance of the control sensor. A final economic evaluation is also performed on the control sensor. It is found that the controller is technically and economically viable in Aotearoa New Zealand.